A Fast Chaos-Based Pseudo-Random Bit Generator Using Binary64 Floating-Point Arithmetic - François, Michael; Defour, David; Negre, Christophe (Informatica, 2014)
Chaos-based cryptography is widely investigated in recent years, especially in the field of random number generators. The paper describes a novel pseudo-random bit generator (PRBG) based on chaotic logistic maps. Three logistic maps are combined in the algorithmic process, and a block of 32 random bits is produced at each iteration. The binary64 double precision format is used according to the IEEE 754-2008 standard for floating-point arithmetic. This generator provides a considerable improvement of an existing generator in the literature. Rigorous statistical analyses are carefully conducted to evaluate the quality and the robustness of the PRBG. The obtained results showed the relevance of the proposed generator, which is suitable even for real-time applications.